Consistent GDP Aggregation and Purchasing Power Parity - Jesus C. Dumagan (Philippine Institute for Development Studies (PIDS), 2012)
Consistent aggregation ensures that real GDP level and growth do not change as the existing GDP components are merely rearranged. Otherwise, level or growth changes are spurious. This paper proposes a framework for consistent aggregation where components are converted to "purchasing power parity" (PPP) values that "add up exactly" to the same real GDP regardless of the grouping of components. This PPP framework applies to GDP either in constant prices or in chained prices. PPP is applied to US GDP in chained prices based on the Fisher index to (i) reduce US nonadditivity residuals to zero; (ii) correct misleading contributions to GDP growth computed by the US Bureau of Economic Analysis; and (iii) show that GDP quantity indexes in PPP are consistent in aggregation although the Fisher formula is inconsistent. Moreover, PPP implications on GDP measurement for some areas of economic research (e.g., income inequality and poverty incidence) are discussed.
Keywords: C43; 330; exact growth decomposition; consistent level aggregation; Nationaleinkommen; Kaufkraftparität; Aggregation; USA